Effect of Metformin and Sitagliptin on Doxorubicin-Induced Cardiotoxicity in Rats: Impact of Oxidative Stress, Inflammation, and Apoptosis - Mina Thabet Kelleni; Entesar Farghaly Amin; Aly Mohamed Abdelrahman (Journal of Toxicology)
Doxorubicin (DOX) is a widely used antineoplastic drug whose efficacy is limited by its cardiotoxicity. The aim of this study was to investigate the possible protective role of the antidiabetic drugs metformin (250 mg/kg dissolved in DW p.o. for seven days) and sitagliptin (10 mg/kg dissolved in DW p.o. for seven days) in a model of DOX-induced (single dose 15 mg/kg i.p. at the fifth day) cardiotoxicity in rats. Results of our study revealed that pretreatment with metformin or sitagliptin produced significant (P<0.05) cardiac protection manifested by a significant decrease in serum levels of LDH and CK-MB enzymes and cardiac MDA and total nitrites and nitrates levels, a significant increase in cardiac SOD activity, and remarkable improvement in the histopathological features as well as a significant reduction in the immunohistochemical expression of COX-2, iNOS, and caspase-3 enzymes as compared to DOX group. These results may suggest using metformin and/or sitagliptin as preferable drugs for diabetic patients suffering from cancer and receiving DOX in their chemotherapy regimen.